2018
DOI: 10.1049/el.2018.0739
|View full text |Cite
|
Sign up to set email alerts
|

Playback speech detection based on magnitude–phase spectrum

Abstract: In current playback speech detection (PSD) Letter, commonly used features are often extracted from magnitude spectrum while phase spectrum information is not used. In order to extract more discriminative information for PSD, the idea of magnitude-phase spectrum (MPS) is proposed. Then a new feature based on MPS is proposed, namely constant-Q magnitude-phase octave coefficients (CMPOC). The experimental result on ASVspoof 2017 evaluation set using CMPOC indicates that: (i) the performance of CMPOC is better tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 10 publications
0
26
0
Order By: Relevance
“…In this study, similar to our previous playback speech detection studies [38,40,41], deep neural network (DNN) is selected as a suitable classifier because we found that DNN based systems can give better performance. The reason may be that DNN has both a classifier function and feature-learning ability [54].…”
Section: Evaluation Rule and Experimental Setupmentioning
confidence: 96%
See 4 more Smart Citations
“…In this study, similar to our previous playback speech detection studies [38,40,41], deep neural network (DNN) is selected as a suitable classifier because we found that DNN based systems can give better performance. The reason may be that DNN has both a classifier function and feature-learning ability [54].…”
Section: Evaluation Rule and Experimental Setupmentioning
confidence: 96%
“…Table 8 gives the comparison with some known systems based on hand-crafted features on ASVspoof 2017 V2 evaluation set. In which, logE represents logarithm energy, qDFTspe represents Q-log domain DFT-based mean normalized log spectral [42], eCQCC represents extended CQCC [38], CMPOC represents constant-Q magnitudephase octave coefficients [40] and CQSPIC represents constant-Q statistics-plus-principal information coefficients [41]. From Table 8, it can be seen that the performance of our systems are better than some other known systems.…”
Section: Comparison With Some Commonly Used Featuresmentioning
confidence: 96%
See 3 more Smart Citations